Intervertebral Disk Degeneration: The Microenvironment and Tissue Engineering Strategies - Dou, Yiming; Sun, Xun; Ma, Xinlong; Zhao, Xin; Yang, Qiang (Frontiers in Bioengineering and Biotechnology, 2021)
Abstract: Intervertebral disc degeneration (IVDD) is a leading cause of disability. The degeneration is inevitable, and the mechanisms are complex. Current therapeutic strategies mainly focus on the relief of symptoms, not the intrinsic regeneration of the IVD. Tissue engineering is a promising strategy for IVDD due to the ability to restore a healthy microenvironment and promote IVD regeneration. This review briefly summarises IVD anatomy and composition and then sets out elements of the microenvironment and the interactions. We rationalised different scaffolds based on tissue engineering strategies used recently. To fulfil the complete restoration of a healthy IVD microenvironment, we propose that various tissue engineering strategies should be combined and customised to create personalised therapeutic strategies for each individual.